The feather mites (Acari, Astigmata) of the Violet-capped Woodnymph, Thalurania glaucopis (Gmelin) (Aves, Trochilidae), with descriptions of three new species - Hernandes, Fabio Akashi [UNESP] (Magnolia Press, 2013)
Six feather mites of the Violet-capped Woodnymph, Thalurania glaucopis are herein reported: Allodectes sejugaspis sp. n., A. thaluraniae sp. n., Trochilodectes brevipenis sp. n., Toxerodectes biscutatus Park and Atyeo (Proctophyllodidae), and two unidentified species from the families Analgidae (Protalginae, genus Protalges) and Ptyssalgidae (genus Ptyssalges). These are the first feather mites to be reported from this host. © 2013 Magnolia Press.
Keywords: Acari; Analgidae; Apodiformes; Hummingbirds; Neotropics; Proctophyllodidae; Ptyssalgidae; Systematic; Taxonomy